(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The transesterification of vegetable oil and/or animal fats in homogeneous alkaline medium is still the most widely used method for the production of biodiesel. However, this process requires raw materials with low acidity and moisture content to prevent undesirable side reactions such as saponification, which leads to emulsification and promotes losses in the reaction yield. Many solid compounds can be used in catalytic processes to reduce these limitations. Heterogeneous catalysts allow easy separation of the reaction media and have the possibility of reuse in several cycles. In this work, [CTA+]MCM-41 molecular sieves were synthesized and characterized by several methods (XRD, SEM, TGA and BET) to be applied in the methanolysis of soybean oil. The resulting materials were characterized as mesoporous solids of type IV with similar textural properties and thermal stability. The catalytic activity of [CTA+]MCM-41 in soybean oil methanolysis was analyzed by gel permeation chromatography (GPC) and the best solid catalyst was applied in a factorial design that was validated by Analysis of Variance (ANOVA). The oil:methanol molar ratio and the catalyst concentration were the variables with the highest statistical effects, with the latter showing a quadratic profile in relation to the response function. The best conversion was achieved at 343 K, 30 min and 3.75 wt % catalyst, which corresponded to a product with 99.2% in fatty acid methyl esters. Calcination caused a total loss in catalytic activity due to the removal of CTA+ cations from the mesoporous solids. Hence, such activity was associated with the formation of (SiO-)(CTA+) ion pairs at the surface of the solid catalyst